PENGEMBANGAN FACEMIST KOMBINASI EKSTRAK DAUN BIDARA (Ziziphus spina cristi (L.) Desf) DAN DAUN BENALU DUKU (Dendrophthoe pentandra (L.) Miq ) SEBAGAI ANTIOKSIDAN PADA KULIT WAJAH - anggara, Elysa; syafitri, anggun; sari, tio ranti (Jurnal Penelitian Farmasi Dan Herbal, 2025)
The skin needs antioxidant compounds that can ward off free radicals caused by several factors, one of which is air pollution. Bidara leaves (Zizipus spina Cristi (L) Desf) and benalu duku leaves (Dendrophthoe pentandra (L.) Miq) contain flavonoid compounds that function as antioxidants that can ward off free radicals. This study aims to formulate bidara leaf extract and benalu duku leaf into the form of Facemist preparation and determine the best Facemist product formula with the addition of bidara leaf extract, benalu leaf, and a combination of two extracts through antioxidant activity parameters. The antioxidant activity test was carried out using the DPPH (1,1-dipenyl-2-picrylhydrazyl) method. The Facemist sample was formulated into a Facemist with concentration variations: F1 : EEDB 5%, F2 : EEDBD : 5%, F3 : EEDB : 2.5% EEDBD 2.5%, F4 : EEDB : 5% EEDBD : 5%, F5 : EEDB : 10% EEDBD : 10%. Facemist preparations are eval_uated for their physical characteristics, namely organoleptic test, homogeneity test, pH test, viscosity test, dry time test, irritation test. The results showed that Facemist was a combination of bidara leaf extract and benalu duku leaf homogeneous, pH <7, had a viscosity value of <500 cps, a good drying time of <5 minutes and did not cause irritation to the skin. The formulation of Facemist preparation that has the best antioxidant activity value is F5 with antioxidant activity (IC50) of 58.33 ppm in the strong category.